STUDENT PROJECT-BASED LEARNING – AN APPROACH TO ENGAGE STUDENT'S MOTIVATION IN HIGHER EDUCATION - Fovi Sriyuliawati (Sean Institute, 2022)
The paper briefly elaborates on student project-based learning related to student motivation, where Project-Based Learning asks students to work in groups over a set period on a project designed to solve a problem or answer a question. Educators have learned an enormous amount that has informed educational practice to enhance learning. The construct of motivation and how to develop positive motivation and behavior has permeated all areas of human endeavor. Educational psychology, in particular, has a long history of studying the nature and dynamics of motivation for learning. (Mclnerney, n.d.). In summary, these articles present very interesting perspectives on students-based project learning and motivation across diverse settings, and they may be further enhanced by significant attention being paid to differences that characterize groups and the specific 'local' features of motivation and learning that must form the foundation of effective educational practices. In other words, a stimulus needs may be considered an attempt to deal with competence getting involved. When we get students' motivation when the PBL pursues a certain goal, remember motivation is not the behavior, it can be directly observed.